Інституційні засади дослідження розвитку туристичної галузі - Збарський, В. К.; Грибова, Діана Вікторівна; Грибова, Диана Викторовна; Hrybova, Diana (My University, 2020)
UK : В статті висвітлено методологічні аспекти розвитку туристичної галузі. Доведено, що в основі становлення інституційного середовища туристичної галузі, знаходяться базові традиції людського суспільства, пов’язані із необхідністю забезпечення розвитку спільноти в біологічному та соціальному аспектах. Обґрунтовано необхідність комплексної участі різних складових інституційного середовища для забезпечення задоволення відповідних суспільних потреб в сфері туризму. Зазначається факт наявність різних класифікаційних підходів до диференціації складових сучасного інституційного середовища. Доведено необхідність застосування системного класифікаційного підходу, який мав би враховувати організаційно-правовий, галузевий та соціально-економічний аспекти функціонування конкретної господарської одиниці. Запропонована класифікація елементів інституційного середовища в сфері туризму. Зазначається, що наведена система критеріїв, у випадку свого комплексного застосування, дозволяє не тільки провести ідентифікацію елементів інституційного середовища конкретного об’єкту туристичної діяльності, а й визначитися із потенційною стратегією щодо співпраці із ними. Вказується на доцільність застосування в процесі подальшого дослідження інституційних аспектів туристичної діяльності методичного інструментарію теорії стейкхолдерів. EN : Methodological aspects of tourism industry development are covered in the article. The specificity of the formation of the institutional society of the leading economies of the world is investigated. It is noted that the longevity of the institute will be determined by the conformity of the stated tasks and functions and the degree of their practical realization in the conditions of socio-economic environment at macro, mes and micro levels. It is proved that the basic traditions of human society are connected with the necessity of ensuring the development of the community in biological and social aspects. It was noted that the consistent process of forming the institutional environment of the tourism business implied the presence of a multilevel system, elements of which not only interact with each other, but also capable of creating new institutions whose functioning is conditioned by constant transformations in the economic and social spheres of society. The necessity of complex participation of different constituents of the institutional environment to ensure satisfaction of relevant public needs in the sphere of tourism is substantiated. It is noted that there are different classification approaches to differentiation of components of the modern institutional environment. The necessity to apply a systematic classification approach, which should take into account the organizational-legal, sectored and socio-economic aspects of the functioning of a particular economic unit, is proved. The classification of elements of the institutional environment in the field of tourism is proposed. It is noted that the system of criteria, in the case of its complex application, allows not only to identify the elements of the institutional environment of a particular tourist activity, but also to determine the potential strategy for cooperation with them. The expediency of applying in the process of further research of the institutional aspects of tourism activities the methodical tools of stakeholder theory is pointed out. Its provisions provide for an analysis of the current state of affairs and an assessment of the prospects for the further development of any business entity, based on the presence of a large number of interested persons who have the ability to influence the nature of economic activity in one way or another.
Institutional resources for the tourist industry development research
Keywords: туризм; інституційний підхід; постіндустріальне суспільство; ефективність; методологія; tourism; institutional approach; post-industrial society; efficiency; methodology